PARP9 and PARP14 cross-regulate macrophage activation via STAT1 ADP-ribosylation - Hiroshi Iwata (Nature Portfolio, 2016)
Signalling pathways that mediate macrophage activation in disease are poorly understood. Here the authors show that inhibition of PARP9 and/or activation of PARP14 may attenuate macrophage-mediated vascular diseases, and also provide new insight into the development of effective therapies for other inflammatory disorders.